CALIDAD DE VIDA Y SATISFACCIÓN DE LOS FAMILIARES DE PACIENTES INGRESADOS EN UNIDADES DE CUIDADOS INTENSIVOS. - da Rosa Viana, Diogo; Brehm Santana, Luísa; de Oliveira Azzolin, Karina; Pinheiro Berto, Paula; Petri Tavares, Juliana; Teixeira, Cassiano; de Souza Silveira, Cristhiane (Cogitare Enfermagem, 2023)
Objective: To evaluate the satisfaction of family members of patients admitted to the Intensive Care Unit and symptoms of anxiety, depression, post-traumatic stress, and quality of life. Method: a longitudinal study with relatives of patients in an Intensive Care Unit in southern Brazil, carried out at two points: after the patient was discharged, followed by three months, using the following instruments: FS-ICU 24, HADS, IES-6, EQ-5D-3L. The analysis was carried out using the Statistical Package for the Social Sciences (SPSS) program. Results: 73/100% of relatives, 58/79.5% of whom were female. Family member satisfaction was 77.42%. There was a significant difference in symptoms of depression (p=0.001), post-traumatic stress (p=0.000) and quality of life, (p=0.007) and "anxiety and depression" (p=0.009) when compared to family members. Anxiety was not significant (p=0.095). Conclusion: Satisfaction with care was satisfactory. Those who lost their loved ones were more depressed, stressed and had worse quality of life scores, thus contributing to clinical practice.